2003
DOI: 10.1161/01.cir.0000066318.21784.43
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volume

Abstract: Background-After acute myocardial infarction (AMI), diastolic function assessed by Doppler echocardiography provides important prognostic information that is incremental to systolic function. However, Doppler variables are affected by multiple factors and may change rapidly. In contrast, left atrial (LA) volume is less influenced by acute changes and reflects subacute or chronic diastolic function. This may be of importance when one assesses risk in patients with AMI. Methods and Results-Three hundred fourteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(109 citation statements)
references
References 24 publications
4
87
0
7
Order By: Relevance
“…11 Furthermore, increased LA size has been shown to be associated with a poor outcome 12 in AS patients undergoing aortic valve replacement, 13 and in various other cardiovascular disorders. [14][15][16][17][18][19][20] Our study demonstrates a close association between LA dilatation and increased PCWP and mPAP at rest and during exercise in patients with AS. We found that in patients with pronounced diastolic dysfunction, PCWP>30 mm Hg at peak exercise were characterized by a very high likelihood of LA dilatation (89%).…”
Section: Discussionsupporting
confidence: 59%
“…11 Furthermore, increased LA size has been shown to be associated with a poor outcome 12 in AS patients undergoing aortic valve replacement, 13 and in various other cardiovascular disorders. [14][15][16][17][18][19][20] Our study demonstrates a close association between LA dilatation and increased PCWP and mPAP at rest and during exercise in patients with AS. We found that in patients with pronounced diastolic dysfunction, PCWP>30 mm Hg at peak exercise were characterized by a very high likelihood of LA dilatation (89%).…”
Section: Discussionsupporting
confidence: 59%
“…18,20 The presence of LA enlargement is an adverse prognostic marker and is associated with increased risk of atrial fibrillation, HF hospitalizations, stroke, and overall cardiovascular mortality. 18,20,[74][75][76][77] Echocardiography is the most commonly used modality for LA volume estimation, and the biplane area-length method is the recommended method for this purpose. 11 Although 3D echocardiography has been demonstrated to be more accurate and more reproducible, [78][79][80] the lack of a standardized methodology limits its routine use.…”
Section: La Dilatation and Dysfunctionmentioning
confidence: 99%
“…В противоположность этому объём левого предсердия (ЛП) менее зависим от острых гемодинамических изменений и отражает подострую или хроническую диастолическую дис-функцию. Прогностическое значение размера и объ-ёма ЛП после ИМ изучалось в нескольких исследова-ниях [28][29][30].…”
Section: прогностическая значимость эхокардиографии после острого инфunclassified
“…Moller JE, et al [29] оценивали объём ЛП, индек-сированный к площади поверхности тела (индекси-рованный объём ЛП) при госпитализации 314 паци-ентов в связи с ОИМ. В течение периода наблюде-ния, составившего в среднем 15 месяцев, 46 па-циентов (15%) умерли.…”
Section: прогностическая значимость эхокардиографии после острого инфunclassified